Melacak Geneologi Keilmuan Masyarakat Jalur Sanad Intelektual Muslim Bengkulu Tahun 1985-2020 - Ahmad Abas Musofa (Indonesian Journal of Islamic History and Culture, 2020)
Socio-religious scholarly in the community are reflected in either daily practice or literary works inherited. Through Muslim intellectuals, the scientific genealogy of society can be traced, either through their educational background or through their knowledge. The purpose of this article is to monitor the scientific genealogy of society through the knowledge of Muslim intellectuals who are active in various institutions and organizations. The historical research method used through four stages, namely heuristics, criticism, interpretation and historiography. Meanwhile, the approach used is intellectual history. This paper pioneered the study of the genealogy of Muslim intellectuals in Bengkulu, which so far received little attention. This is based on the results of studies related to Bengkulu Muslim intellectuals that have not been monitored on this issue. The important finding in this paper is that the scientific nature of each Muslim intellectual is different, but all sanad of the Muslim intellectuals are connected to the Prophet. The following is the scientific genealogy of society that is traced through sanad, they are tarekat (Syatariyah, Naqsyabandiyah, Qadiriyah wa Naqsyabandiyah, Syadziliyah), sanad al-Quran, sanad Hadith and sanad kitab.